Exploring dualities of service innovation: implications for service research. Issue 6 (14th September 2015) - Witell, Lars; Anderson, Laurel; Brodie, Roderick J.; Colurcio, Maria; Edvardsson, Bo; Kristensson, Per; Lervik-Olsen, Line; Sebastiani, Roberta; Wallin Andreassen, Tor
Abstract : Purpose: – The purpose of this study is to explore three paradoxes of service innovation and provide a way forward for fresh thinking on the topic. Design/methodology/approach: – Through a conceptual model of service innovation research, the authors challenge the "pro-change" bias and explore what can be learnt from the duality of service innovation. Findings: – This paper suggests that research moves beyond a firm perspective to study service innovation on multiple levels of abstraction. A conceptual model based on two dimensions, level (individual, organization and society) and outcome (success, failure), is used to pinpoint and explore three dualities of service innovation: adopt–reject, change–static and good–bad. Originality/value: – By challenging the traditional perspective on service innovation, the authors present new avenues for fresh thinking in research on service innovation. In this paper, the authors encourage researchers and managers to learn from failures and to acknowledge the negative effects of service innovation.